2020
DOI: 10.1038/s41598-020-76700-3
|View full text |Cite
|
Sign up to set email alerts
|

New challenges for efficient usage of Sargassum fusiforme for ruminant production

Abstract: Sargassum fusiforme, which is a type of brown algae, can provide fiber and minerals to ruminant diets. In this study, dried S. fusiforme was tested in vitro at four different doses 1, 3, 5, and 10% of the total ration for its effect on ruminal fermentation characteristics, and gas profiles when incubated for 72 h. At a level of 1 and 10%, S. fusiforme supplementation augmented total volatile fatty acid (VFA) concentrations compared to that with 0% supplementation. In addition, total gas, methane, and carbon di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
3
13
2
Order By: Relevance
“…[ 40 ] This study also revealed that by providing 1–10% inclusion rate of S. fusiforme , volatile fatty acid (VFA) concentration increased significantly and that helped in reducing total CH 4 emissions. [ 40 ] These studies discussed the possibility of shifting the metabolic pathways of methane producing bacteria but need further analysis. All these examples suggest that seaweed complex carbohydrates could be used to reduce CH 4 production from ruminants.…”
Section: Carbohydratesmentioning
confidence: 94%
See 1 more Smart Citation
“…[ 40 ] This study also revealed that by providing 1–10% inclusion rate of S. fusiforme , volatile fatty acid (VFA) concentration increased significantly and that helped in reducing total CH 4 emissions. [ 40 ] These studies discussed the possibility of shifting the metabolic pathways of methane producing bacteria but need further analysis. All these examples suggest that seaweed complex carbohydrates could be used to reduce CH 4 production from ruminants.…”
Section: Carbohydratesmentioning
confidence: 94%
“…[ 11 ] Another important study on specific polysaccharides including the anionic sulfated polysaccharide fucoidan, carboxylated polysaccharide alginate, laminarin, and mannitol found in brown seaweed ( S. fusiforme ) resulted in decreased CH 4 production by providing fiber and minerals to the ruminant diets. [ 40 ] This study also revealed that by providing 1–10% inclusion rate of S. fusiforme , volatile fatty acid (VFA) concentration increased significantly and that helped in reducing total CH 4 emissions. [ 40 ] These studies discussed the possibility of shifting the metabolic pathways of methane producing bacteria but need further analysis.…”
Section: Carbohydratesmentioning
confidence: 94%
“…Feed was offered at 8:30 a.m. and 5:00 p.m. Ruminal fluid was collected and mixed before morning feeding from two Hanwoo cows. After passing through it using 4 layers of cheese cloth, it was placed in an insulated bottle maintained at 39 • C and moved to the laboratory in a vacuum state [19]. Rumen fluid was mixed with McDougall's buffer [20] artificial saliva in a ratio of 1:2 (V:V).…”
Section: In Vitro Batch Fermentationmentioning
confidence: 99%
“…Recent animal feed research has focused on creating substitutes for conventional feed components to minimize environmental and financial concerns. Algae are a desirable feed source with several potential uses outside the realm of human eating (Choi et al, 2020b). Sargassum sp.…”
Section: Introductionmentioning
confidence: 99%